PENGARUH METODE EKSTRAKSI KENCUR (Kaempferia galanga L.) TERHADAP PERTUMBUHAN Staphylococcus aureus - Sri Nopita Primawati; Husnul Jannah (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Kaempferia galanga L. or known as Kencur is an herbal plant that is widely used by people with various benefits such as influenza in infants, headaches, sprains, relieving fatigue, inflammation of the stomach, coughing, improving menstruation, inflammation of children's ears, dirty blood, eyes aches, diarrhea, and colds. However, studies that have used Kencur as an antibacterial against Staphylococcus aureus have never been done. Therefore, scientific research is needed to determine the ability of Kencur extract as an antibacterial that inhibits the growth of Staphylococcus aureus. 3 extraction methods were used, with the aim of determining the right method for obtaining Kencur bioactive compounds as antibacterial. The three extraction methods used were the press method, the infusion method, and the maceration method using methanol as a solvent. Each extract obtained from various extraction methods will be tested for antibacterial by observing the growth of Staphylococcus aureus. It was found that with the press method there were no clear zones or growth inhibition zones of Staphylococcus aureus. Using the extract from the infusion method, the same thing is obtained, namely there is no clear zone or growth inhibition zone of Staphylococcus aureus. However, it is different when given an extract from the maceration method using methanol solvent, a 17 mm clear zone is formed but there is no inhibition zone. This can indicate that, methanol extract from Kencur can inhibit the growth of Staphylococcus aureus (17 mm).